Analysis of Protein and Fat Content in Beef Meatballs Sold in the Kefamenanu City - Dionicio Natalino Kolo; Kristoforus W. Kia; Paulus Klau Tahuk (Journal of Tropical Animal Science and Technology, 2023)
This study aims to analyze the protein content and fat content of meatballs sold in the city of kefamenanu. This research has been carriend out at the architektural livestock chemistry laboratory Nusa Cendana University. The methods Used to measure the protein content and fat content are Soxhlet Extraction Method and the Macro-Kjehldahl Method. The variables observed were the protein content and fat content sold in the city of Kefamenanu. The data obtained were tabulated using tables and graphs and then analyzed descriptively. The results of this study indicate that the protein content and fat content of beef meatballs circulating in the city of kefamenanu has a protein content below the SNI standard, while the fat content of beef meatballs has met SNI standard.